Effect of ball milling process on the mechanical and thermal properties of the nanodiamond/2024Al composites. (September 2021) - Huang, Junjie; Zhang, Yazhou; Wang, Defa; Ren, Bo; Song, Panying; Zhang, Guopeng; Cai, Bin; Liu, Zhongxia
Highlights: NDs increases the compressive yield strength (σyc ) and decreases the thermal expansion coefficient (CTE) of 2024Al. The ball milling increases the the σyc due to it enhances fine grain strengthening and the dispersion strengthening. The ball milling decreases the CTE due to it decreases the internal stress and increases the constraint of NDs on α-Al. α = σ ycC ⋅ ε k c C σ y c M ⋅ ε k c M ⋅ C T E M C T E C can be used to evaluate the synergistic influence of mechanical properties and CTEs on the dimensional stability. The σyc and CTEs increases by 95–100 % and decreases by 30–35 % respectively using the optimal ball milling processes. Abstract: In this study, 5 wt.% nanodiamond (ND) reinforced 2024Al matrix composites (ND/2024Al) were fabricated with various ball milling processes. The microstructure, compressive yield strength (σyc ) and coefficient of thermal expansion (CTE) of ND/2024Al composites were investigated. It is found that the addition of 5 wt.% NDs significantly increases the σyc and decreases the CTE of 2024Al. High energy ball milling further increases σyc and decreases CTEs of ND/2024Al composite due to it enhances the fine grain strengthening of α-Al matrix and the dispersion strengthening of NDs, decreases the thermal mismatch stress at the ND/α-Al matrix interface, and increases the constraint of NDs on α-Al. The composites fabricated by the combinations of ball milling speeds and times of (5−7) h×(200−250)rpm and 9 h×300 rpm have the highest σyc and the lowest CTE respectively. Considering the different influence of ball milling parameters on σyc and CTEs, a evaluation coefficient α = σ ycC ⋅ ε k c C σ y c M ⋅ ε k c M ⋅ C T E M C T E C is proposed to evaluate the synergistic influence of mechanical properties and CTEs on the dimensional stability of ND/2024Al composites. Large value of α may lead to high dimensional stability of material, hence the α can be used to determine the ball milling parameters.The ball milling process of 250−300 rpm ball milling speeds and 5−7 h ball milling times are recommended based on α, which causes a 95–100 % increase in σyc and a 30–35 % decrease in CTE compared with 2024Al alloy, respectively.